A Proposed Model for Infant and Child Oral Health Promotion in India - Ashwin Muralidhar Jawdekar (International Journal of Dentistry)
Dental caries is an increasing burden in the developing countries. A proper budgetary allocation for treating dental diseases in an enormous population such as India is impractical, where resources are inadequate for major health challenges such as malnutrition and gastrointestinal and respiratory infections in children. An integrated, directed population approach targeting children is much needed. The existing machinery of successful public health campaigns such as the “Pulse Polio” and the “Mid-Day-Meals Scheme” of the Government of India can be used for oral health promotion for children. India has about 300 dental colleges and countrywide branches of the Indian Dental Association that can provide manpower for the program. An innovative, large-scale “Fit for School” program in Philippines is a model for an integrated approach for children’s health and has proved to be cost-effective and viable. A model for oral health promotion in infants and children of India, combining age-specific initiatives for health education, nutrition, hygiene, and fluoride use, is proposed. The model could be implemented to evaluate the oral health status of children, knowledge and knowledge gain of the community health workers, and acceptability and sustainability of the preventive programs (fluoride varnish and preschool and school tooth brushing) pragmatically.